COVID-19 e Geografia: perplexidade atual e a cartografia a serviço da saúde pública - Paula Lindo; Éverton de Moraes Kozenieski; Reginaldo José de Souza (Confins)
The perplexity of the new coronavirus pandemic is present in our daily lives and calling for sciences to minimize the impacts of COVID-19 on public health. Geography, knowledge located between social and natural events, is faced with a necessary reinterpretation of the meaning of Nature's dynamics in situations that show their power above the society, even with all the contemporary technical-scientific-informational apparatus. SARS-CoV-2 has been metabolized in the technological network worldwide and this generates catastrophic results in several locations on the planet. In this article, we have two aims: to discuss about the new epistemic horizon for Geography in the present planetary challenge. Then, we jump from the global reflection about pandemic to the prognosis of possible consequences in the city in wich we live and we seek to understand its socio-spatial organization in a critical way: Erechim, Rio Grande do Sul. The methodological strategy was the elaboration of thematic maps from indicators of population distribution by age group, demographic density and number of residents in the houses. This selection was motivated by the fact that elderly people form a risk group in cases of infection and the agglomerations facilitate transmissions. The maps produced show the distribution of the elderly throughout the city, with a greater concentration in the central sectors, and identify households habited by more than six people in the periphery. Information was compared with a social exclusion / inclusion map and the result is a synthesis map for priority actions against COVID-19 in Erechim city. Keywords: nature, space, coronavirus, map, Erechim.